2021
DOI: 10.1007/s13201-021-01494-2
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the impact of climate change on runoff and drought in an arid and semiarid basin (the Hablehroud, Iran)

Abstract: This study evaluates the impact of climate change (CC) on runoff and hydrological drought trends in the Hablehroud river basin in central Iran. We used a daily time series of minimum temperature (Tmin), maximum temperature (Tmax), and precipitation (PCP) for the baseline period (1982–2005) analysis. For future projections, we used the output of 23 CMIP5 GCMs and two scenarios, RCP 4.5 and RCP 8.5; then, PCP, Tmin, and Tmax were projected in the future period (2025–2048). The GCMs were weighed based on the K-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…Therefore, it can be concluded that the omission of some models and the use of a limited number of them cannot provide a reliable estimate of runoff and climatic variables in the future. This result is consistent with the statements (Alinezhad et al, 2021;Ashrafi et al, 2020;Lotfirad et al, 2021). Therefore, in this study, the BMA method was used to maintain the capacity of all models and reduce the uncertainty caused by using a single model (Najafi et al, 2011).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Therefore, it can be concluded that the omission of some models and the use of a limited number of them cannot provide a reliable estimate of runoff and climatic variables in the future. This result is consistent with the statements (Alinezhad et al, 2021;Ashrafi et al, 2020;Lotfirad et al, 2021). Therefore, in this study, the BMA method was used to maintain the capacity of all models and reduce the uncertainty caused by using a single model (Najafi et al, 2011).…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the IHACRES semi-conceptual model simulated the rainfall-runoff process. This model consists of two modules, linear and nonlinear, which convert PCP into effective PCP and effective PCP into the runoff, respectively see Jakeman & Hornberger (1993) and Lotfirad et al (2021). For rainfall-runoff simulations in this study, the 19-year period (1994 to 2012) was considered as the calibration period, and the 7-year period (2013 to 2018) was considered as the validation period.…”
Section: Ihacres Rainfall-runoff Modelmentioning
confidence: 99%
See 3 more Smart Citations